PEMBERDAYAAN MASYARAKAT DENGAN MENCIPTAKAN LAPANGAN USAHA BARU MELALUI PROGRAM SOCIAL PRENEUR DENGAN METODE ECOFARMING DI DE DESA OLOBOJU - Fadlhi, Wendy Muhammad; Matoka, Natasya S.; Astrid, Ratri; Mukaromah, Lailatul; Faradillah, Faradillah; Kristiani, Kristiani; Alamsah, Asniati; Tumanan, Indriartri; Misra, Misra; Butudoka, Eka Pratiwi K; Zaitun, Zaitun; Ramadani, Gina (Jubaedah : Jurnal Pengabdian dan Edukasi Sekolah (Indonesian Journal of Community Services and School Education), 2025)
The Ornawa Mernbangun Negeri program aims to improve the welfare of the Oloboju Village community through ecofarming-based social entrepreneurs, especially rabbit farming. This activity includes location surveys, licensing, counseling, training, and evaluation. The training focuses on rabbit care, including balanced feeding, cage cleanliness, and conducive environmental management. The evaluation results showed a significant increase in the level of community knowledge regarding rabbit farming, with the "good" category increasing from 46.7% to 100% after training. This program is effective in creating new jobs while increasing the community's ability to manage local potential independently